Pengaruh Pelatihan dan Komunikasi Internal terhadap Employee Engagement pada Departemen Makanan dan Minuman di Masa Pandemi Covid-19 - Yuda, I Wayan Prananda Hendra; Artajaya, Made; Hardina, Hardina (HeadWay Research & Developemnt, 2024)
This study aims to analyze (1) the effect of training on employee engagement, (2) the effect of internal communication on employee engagement, and (3) the effect of training and internal communication simultaneously on employee engagement at the Hotel in Bali during Covid-19 pandemic. The number of samples in this study were 38 respondents using the saturated sample technique. Data was collected by distributing questionnaires to respondents using Google Form as the media. The data analysis technique used is the Classical Assumption Test, Multiple Linear Regression Analysis, t-test, F-test, Coefficient of Determination, and Effective Contribution which were tested using the SPSS version 25 program. The results of this study indicate that (1) the training variable partially has a positive and positive effect. significant on employee engagement variable with t-count > t-table (2.053 > 1.689) and Sig. 0.048 < 0.05. (2) the internal communication variable partially has a positive and significant effect on exit intentions with a t-count < t-table (10.558 < 1.689) and a Sig value. 0.000 < 0.05, and (3) training and internal communication simultaneously have a positive and significant effect on employee engagement with a significance of 0.000